Allo-HSCT with TBI-based preconditioning for hepatosplenic T-cell lymphoma: two case reports and systematic review of literature - Chen, Can; Yang, Fan; Miu, Peiwen; Shi, Pengfei; Qian, Shenxian (Frontiers in Oncology, 2024)
Hepatosplenic T cell lymphoma (HSTCL) is a particularly difficult-to-treat form of lymphoma, with many patients exhibiting primary resistance to chemotherapy. At present, no effective strategy for treating relapsed and refractory HSTCL has been established, with treatment being hampered by questions of how best to overcome chemoresistance to allow patients to attain more durable therapeutic benefits. While there have been marked advances in immunotherapy, allogeneic hematopoietic stem cell transplantation (allo-HSCT) remains one of the primary approaches to curing HSTCL. Of patients who undergo immunochemotherapeutic treatment, many are resistant to conventional chemotherapeutic drugs yet remain sensitive to radiotherapy. We selected to employ a transplant pretreatment regimen consisting of total -body irradiation (TBI) and administered this regimen to two patients with HSTCL. Both patients achieved complete remission (CR) after transplantation, demonstrating extended periods without disease recurrence. We systematic reviewed previously published instances involving allo-HSCT in patients with HSTCL. We have found a total of 67 patients who have received allo-HSCT. In general, age<45 and the status of CR at HSCT may have a more favorable prognosis. Although the impact of TBI on prognosis was not found to be substantial, patients in the TBI group had higher 3-year overall survival (66.7% vs. 71.1%) and 5-year overall survival (58.4% vs. 71.1%) compared to patients in the non-TBI group. In addition, the relapse rate of the TBI group is approximately half that of the non-TBI group. This regimen is well tolerated and associated with low recurrence rates or complications, suggesting that it represents a viable pretreatment regimen for young HSTCL patients undergoing allogeneic HSCT.